Sex Differences in Insulin-Induced Hippocampus Functional Connectivity During Visual Food-Cue Presentation - Zhao, Sixiu; Veit, Ralf; Semeia, Lorenzo; Hummel, Julia; Sandforth, Leontine; Fritsche, Andreas; Birkenfeld, Andreas L; Heni, Martin; Preissl, Hubert; Kullmann, Stephanie (The journal of clinical endocrinology and metabolism, 2025)
Central insulin has been shown to regulate eating behavior and cognitive processes in a sex-specific manner. Besides memory, the hippocampus is pivotal in the control of appetite. This work aimed to investigate how insulin interacts with the hippocampal food-cue response and evaluate the potential role of sex hormones. Using functional magnetic resonance imaging, we evaluated task-based functional connectivity (FC) of the hippocampus during food-cue presentation in 60 participants (age: 21-69 years; 30 women) after intranasal insulin or placebo administration, in a randomized within-subject design. In an exploratory analysis, we investigated whether hippocampal FC after intranasal insulin administration is related to estradiol and progesterone levels during the follicular and luteal phase of the menstrual cycle in 13 premenopausal women (age: 20-28 years). Intranasal insulin increased hippocampal FC with the prefrontal cortex compared to placebo, regardless of sex. This correlated with stronger reduction in subjective feeling of hunger and food craving. Moreover, we observed an interaction between sex and nasal spray condition with higher hippocampal FC to the calcarine gyrus after insulin compared to placebo in men, while women showed a lower response. In premenopausal women, the centrally mediated effect of insulin on hippocampus to calcarine gyrus FC negatively correlated with the estradiol/progesterone ratio in the luteal phase. Central insulin influences hippocampal FC to regions vital for inhibitory control during high-caloric food-cue presentation, implying a potential role of the hippocampal network in modulating insulin's anorexic effects. The observed sex differences between the hippocampus and visual cortex might be influenced by sex hormone action.